COMMON MISTAKES MADE BY FORENSIC EXAMINERS WHEN CONDUCTING HUMAN TRACE EVIDENCE EXAMINATIONS AND DOCUMENTING THEIR RESULTS - E. Burova (Теория и практика судебной экспертизы, 2015)
The paper reviews the most common terminology and documentation mistakes in forensic expert reports on the outcomes of examinations classified under specialization 6.1 «Forensic examination of trace evidence of human and animal origin», and offers recommendations for elimination of such errors.